2019
DOI: 10.3390/met9050601
|View full text |Cite
|
Sign up to set email alerts
|

Roasting Pretreatment Combined with Ultrasonic Enhanced Leaching Lead from Electrolytic Manganese Anode Mud

Abstract: A method of conventional roasting pretreatment combined with ultrasonic enhanced leaching with ammonium acetate was proposed to solve the difficult problem of lead in electrolytic manganese anode mud. The effects of concentration, liquid–solid ratio, temperature, leaching time and rotating speed on the leaching process under conventional and ultrasonic conditions were studied, and the lead leaching rate can be as high as 93.09% under optimized process parameters. A leaching kinetic model under conventional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this study, flaky tinplate scraps with a size of 2 cm × 2 cm were used in the leaching process. The unreacted shrinking core model is generally used to characterize the leaching kinetic mechanism for the granular material [22] . The Sn dissolution process from the surface of flaky tinplate scraps has the following features, 1) the thickness of tinplate scraps used in this study is uniform; 2) the insoluble iron matrix has good structural strength, and it is inert in the alkaline solution; 3) the solute diffusion direction is perpendicular to the particle thickness direction.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, flaky tinplate scraps with a size of 2 cm × 2 cm were used in the leaching process. The unreacted shrinking core model is generally used to characterize the leaching kinetic mechanism for the granular material [22] . The Sn dissolution process from the surface of flaky tinplate scraps has the following features, 1) the thickness of tinplate scraps used in this study is uniform; 2) the insoluble iron matrix has good structural strength, and it is inert in the alkaline solution; 3) the solute diffusion direction is perpendicular to the particle thickness direction.…”
Section: Resultsmentioning
confidence: 99%
“…A technically reasonable and efficient treatment of EMAS for rapid and synchronous manganese Mn, Pb, Sn, and Se separation via sulfidation transformation and leaching was proposed in Figure 7. Furthermore, under ultrasonic conditions, the lead leaching efficiency can be increased from 86.98% to 96.36%, as reported by Xie et al 39,52 Zhang 15 also observed that impurity ions can be removed while maintaining the solid form of manganese compounds by choosing an appropriate leachate. This excellent result was achieved at a reduction temperature of 950 °C, carbon mass ratio of 10%, and holding time of 100 min.…”
Section: Recovery and Separation Of Pbmentioning
confidence: 67%
“…Lead (Pb) is a significant industrial raw material, which has been extensively used in our daily life, for instance, batteries, cables, and chemical products [132] , [133] . The leaching characteristics of Pb from various secondary resources with the assistance of ultrasound are summarized and compared in Table 5 .…”
Section: Applications Of Ultrasound Technology In Metal Leaching Proc...mentioning
confidence: 99%
“…The leaching characteristics of Pb from various secondary resources with the assistance of ultrasound are summarized and compared in Table 5 . At present, ultrasound has been introduced into the hydrometallurgical recovery of Pb from secondary resources, such as lead-rich oxidizing slag, fly ash, solid waste incineration fly ashes, waste printed circuit boards, landfilled metallurgical residues, electrolytic manganese anode mud and industrial waste sludges [39] , [73] , [75] , [100] , [111] , [132] , [134] , [135] to remove the residual Pb and eliminate the potential environmental pollution. Zhang et al [75] optimized the leaching conditions of Pb from antimony and lead-rich oxidizing slag in HCl-NaCl media with the assistance of ultrasound.…”
Section: Applications Of Ultrasound Technology In Metal Leaching Proc...mentioning
confidence: 99%
See 1 more Smart Citation